Identification of potential inhibitors of Trichomonas vaginalis iron-containing superoxide dismutase by computer-aided drug design approach - MUTLU, ÖZAL (SPRINGER/PLENUM PUBLISHERS, 2021)
Trichomonas vaginalis is a human protozoan parasite that causes trichomoniasis, a common sexually transmitted disease. Metronidazole is a commonly used drug for the treatment of T. vaginalis infections. However, it was reported that the parasite has developed resistance to this drug. Therefore, a necessity of discovering new drugs that have different modes of action against T. vaginalis has emerged. In this computational study, T. vaginalis iron-containing superoxide dismutase (TvSOD) was selected as target protein because of its vital role in converting superoxide to oxygen and hydrogen peroxide and protecting the parasite against toxic reactive oxygen species (ROS). TvSOD was modeled using two different protein modeling programs, MODELLER and SWISS-MODEL, and then, small drug-like chemicals were screened for interaction with three different druggable pockets of the enzyme. The best interacting chemicals were then evaluated through molecular dynamics simulations (MDSs) for ligand stability. As a result, ligand-129817054 (7-(6-amino-1,2,3,4,5-pentahydroxyhexyl)-4-methylchromen-2-one) was determined to be a viable drug candidate based on docking scores and MDS results. Additional in vitro inhibition studies are necessary for the evaluation and assessment of the compound of interest as an effective TvSOD inhibitor.
Keywords: Computer-aided drug design; Trichomonas vaginalis; Superoxide dismutase; Virtual screening